Optimization of a new chemiluminescence sensor based on peroxyoxalate chemiluminescence - Omanović, Enisa; Moderegger, Helmut; Kalcher, Kurt (Univerzita Pardubice, 2005)
The optimization of the experimental conditions for using new single-shot sensors based on chemiluminescence (CL) with two oxalate esters is presented. The new sensors are suitable for the determination of hydrogen peroxide in different kinds of samples. Each sensor contains an oxalic acid ester, a fluorescer, and a polymer. Bis (2,4-dinitrophenyl) oxalate (DNPO) and bis (2, 4, 6-trichlorophenyl) oxalate (TCPO) are used as esters in chemiluminescent reagents. The fluorescer and the polymer in both systems was 9, 10-diphenylanthracene and cellulose acetate. The polymeric membrane on a transparent glass support contained reactants and was placed over a photocell as detector, the sample was directly applied onto the membrane. The composition of the membrane was optimized. The sensors will be tested on samples of commercially available washing powders.
Keywords: chemiluminiscence; senzory; peroxo-sloučeniny; oxaláty